Safety and efficacy of Durvalumab with or without Tremelimumab in patients with PD-L1-low/negative recurrent or metastatic HNSCC: the phase 2 CONDOR randomized clinical trial - Siu, Lillian L.; Krauß, Jürgen (JAMA oncology, 2019)
Importance: Dual blockade of programmed death ligand 1 (PD-L1) and cytotoxic T-lymphocyte associated protein 4 (CTLA-4) may overcome immune checkpoint inhibition. It is unknown whether dual blockade can potentiate antitumor activity without compromising safety in patients with recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) and low or no PD-L1 tumor cell expression. Objective: To assess safety and objective response rate of durvalumab combined with tremelimumab. Design, Setting, and Participants: The CONDOR study was a phase 2, randomized, open-label study of Durvalumab, Tremelimumab, and Durvalumab in Combination With Tremelimumab in Patients With R/M HNSCC. Eligibility criteria included PD-L1-low/negative disease that had progressed after 1 platinum-containing regimen in the R/M setting. Patients were randomized (N = 267) from April 15, 2015, to March 16, 2016, at 127 sites in North America, Europe, and Asia Pacific. Interventions: Durvalumab (20 mg/kg every 4 weeks) + tremelimumab (1 mg/kg every 4 weeks) for 4 cycles, followed by durvalumab (10 mg/kg every 2 weeks), or durvalumab (10 mg/kg every 2 weeks) monotherapy, or tremelimumab (10 mg/kg every 4 weeks for 7 doses then every 12 weeks for 2 doses) monotherapy. Main Outcomes and Measures: Safety and tolerability and efficacy measured by objective response rate. Results: Among the 267 patients (220 men [82.4%]), median age (range) of patients was 61.0 (23-82) years. Grade 3/4 treatment-related adverse events occurred in 21 patients (15.8%) treated with durvalumab + tremelimumab, 8 (12.3%) treated with durvalumab, and 11 (16.9%) treated with tremelimumab. Grade 3/4 immune-mediated adverse events occurred in 8 patients (6.0%) in the combination arm only. Objective response rate (95% CI) was 7.8% (3.78%-13.79%) in the combination arm (n = 129), 9.2% (3.46%-19.02%) for durvalumab monotherapy (n = 65), and 1.6% (0.04%-8.53%) for tremelimumab monotherapy (n = 63); median overall survival (95% CI) for all patients treated was 7.6 (4.9-10.6), 6.0 (4.0-11.3), and 5.5 (3.9-7.0) months, respectively. Conclusions and Relevance: In patients with R/M HNSCC and low or no PD-L1 tumor cell expression, all 3 regimens exhibited a manageable toxicity profile. Durvalumab and durvalumab + tremelimumab resulted in clinical benefit, with minimal observed difference between the two. A phase 3 study is under way. Trial Registration: clinicaltrials.gov Identifier:NCT02319044